Practical Web Development with Haskell Master the Essential Skills to Build Fast and Scalable Web Applications - Putrady, Ecky (Apress, 2018)
Learn how to advance your skill level of Haskell, and use this language for practical web development. This book uses a direct, no nonsense approach, so you no longer need to spend extra time reading the documentation, blog posts, and forums to understand how to use Haskell - all that knowledge is provided in one coherent resource. You'll start by reviewing how multiple facets of web development are done in Haskell, such as routing, building HTMLs, interacting with databases, caches, and queues, etc. You'll then move on to using notable libraries, such as "scotty" for routings, "digestive-functor" for input validation, and "postgresql-simple" for interacting with databases. In the later chapters, you'll learn how all of these libraries can be used together by working on a fully functioning project deployed on Heroku. .